2023
DOI: 10.4103/aja20238
|View full text |Cite
|
Sign up to set email alerts
|

Altered microRNA expression profiles of human spermatozoa in normal fertile men of different ages

Abstract: MicroRNAs (miRNAs) are mediators of the aging process. The purpose of this work was to analyze the miRNA expression profiles of spermatozoa from men of different ages with normal fertility. Twenty-seven donors were divided into three groups by age (Group A, n = 8, age: 20–30 years; Group B, n = 10, age: 31–40 years; and Group C, n = 9, age: 41–55 years) for high-throughput sequencing analysis. Samples from 65 individuals (22, 22, and 21 in Groups A, B, and C, respectively) were used for validation by quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Exposure to MPs/NPs activates the Hippo and MAPK signaling pathways, influencing cell proliferation and causing reproductive toxicity in mice. , Our sequencing data indicated significant changes in several miRNAs linked to reproductive genetics. Enrichment analysis revealed that age-related miRNAs, such as mmu-miR-1983 and mmu-miR-5100, which are strongly associated with the Hippo and MAPK signaling pathways, were downregulated, suggesting that male fertility declines with increasing age . In addition, our study found that mmu-miR-1983 and mmu-miR-5100 were significantly associated with genes related to reproductive toxicity, potentially affecting the Hippo and MAPK signaling pathways.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Exposure to MPs/NPs activates the Hippo and MAPK signaling pathways, influencing cell proliferation and causing reproductive toxicity in mice. , Our sequencing data indicated significant changes in several miRNAs linked to reproductive genetics. Enrichment analysis revealed that age-related miRNAs, such as mmu-miR-1983 and mmu-miR-5100, which are strongly associated with the Hippo and MAPK signaling pathways, were downregulated, suggesting that male fertility declines with increasing age . In addition, our study found that mmu-miR-1983 and mmu-miR-5100 were significantly associated with genes related to reproductive toxicity, potentially affecting the Hippo and MAPK signaling pathways.…”
Section: Discussionmentioning
confidence: 60%
“…Enrichment analysis revealed that agerelated miRNAs, such as mmu-miR-1983 and mmu-miR-5100, which are strongly associated with the Hippo and MAPK signaling pathways, were downregulated, suggesting that male fertility declines with increasing age. 57 In addition, our study found that mmu-miR-1983 and mmu-miR-5100 were significantly associated with genes related to reproductive toxicity, potentially affecting the Hippo and MAPK signaling pathways. A pronounced decrease in mmu-miR-6240 levels was observed in F 0 sperm with exposure to particulate matter with a diameter of less than 2.5 μm (PM 2.5 ), which could lead to intergenerational primary hypogonadism in offsprings.…”
Section: Discussionmentioning
confidence: 63%
“…miRNAs are pivotal in influencing age-related changes in male fertility and may provide valuable insights into the mechanisms driving the decline in fertility as men age. Zhao et al analyzed changes in miRNA expression profiles of human spermatozoa and discovered that hsa-miR-7977 expression increases with age [ 41 ]. This finding suggests that elevated hsa-miR-7977 levels may be linked to poor sperm quality.…”
Section: Discussionmentioning
confidence: 99%